Detection and tracking of moving targets in phased array radar - Chung, Wen Hao (2016)
This report describes the project titled, Detection and Tracking of Moving Targets in Phased Array Radar. The intent of this project is to improve the detectability and tractability in phased array radar. After the fundamental studies on phased arrays and target detection and tracking, a technique was identified to improve the detectability and tractability in phased array radar. Simulation software, Matlab (r2015b), was used to describe the proposed technique in details. During target detection and tracking, it is boon for the main beam to have its gain as high as possible with half gain beam width as narrow as possible. It was found that the increase in the total number of elements used in phased array radar would only allow a logarithmic increase in gain with half gain beam width converges to a constant. Hence, a possible technique of using multi-beam deployment in phased array radar was proposed. The technique partitioned the phased array virtually into smaller array, called sub-array. As such, it enabled multi-beam deployment. The validation of Matlab script was to ensure the integrity of the proposed technique simulation results. The validation looked at the windowing and phase sequences required for each element to achieve the desired beam pattern. An algorithm was designed to decide if multi-beam deployment was viable during the scan interval for multiple targets detection and tracking. The algorithm made use of predetermined number of deployable beams and estimated gain for each target during the decision making process. As the constructive and destructive interference between sub-arrays affect the main beam characteristics, investigations on the proposed scheme were carried out to describe its limitations, performances trade-off and advantages. Its limitations were associated with its key parameter and constraint. Although there were mixed results on its trade-off, there were numerous advantages of the proposed scheme. Such as, it could be implemented on a conventional system without any hardware modification. All in all, the aim to improve the detectability and tractability in phased array radar has been met.